Analysis of biomonitoring data to assess employer compliance with OSHA's permissible exposure limits for air contaminants. Issue 2 (5th December 2021) - Tustin, Aaron W.; Cannon, Dawn L.
Abstract: Background: The Occupational Safety and Health Administration (OSHA) regulates exposures to hazardous chemicals in workplace air. When contemporaneous exposure measurements are unavailable, retrospective analysis of biomarkers could provide valuable information about workers' exposures. Methods: Single‐compartment pharmacokinetic (PK) models were created to relate the concentration of a chemical in the air to the concentration of the chemical or its metabolite in workers' blood or urine. OSHA utilized the PK models in investigations of three fatal incidents in which workers were exposed to nickel carbonyl, methyl bromide, or styrene. To obtain the minimum plausible estimate of each exposure, OSHA used conservative assumptions about parameters such as workers' inhalation rates, baseline levels of biomarker, and chemicals' volumes of distribution. Results: OSHA analyzed a worker's urinary nickel concentration and concluded that his 8‐h time‐weighted average exposure to nickel carbonyl was at least 0.06 mg/m 3 . Analysis of a worker's postexposure, premortem blood bromide level revealed that his exposure to methyl bromide was at least 181 mg/m 3 . Post‐mortem blood styrene measurements suggested that a third worker's exposure to styrene was at least 625 mg/m 3 . These exposures exceeded OSHA's permissible exposure limits of 0.007 mg/m 3 for nickel carbonyl, 80 mg/m 3 for methyl bromide, and 426 mg/m 3 for styrene. OSHA successfully cited the three employers for violations of chemical exposure limits. Conclusions: Analysis of biomarkers via PK modeling enables retrospective evaluations of workers' acute exposures to hazardous chemicals. These techniques are useful to occupational regulators who assess employer compliance with mandatory exposure limits.